Análise do perfil epidemiológico dos pacientes submetidos a tratamento cirúrgico do carcinoma bem diferenciado da tireoide em hospital terciário - Rocha, Ricardo Mai (2016)
Introduction: The well-differentiated thyroid carcinoma (WDTC) corresponds to 90% of all the existing thyroid malignant neoplasm. The primary therapy for differentiated thyroid cancer is surgery. The efficiency of the surgical therapy is one the main prognostic factors in the evolution of the disease. Objective: Study the epidemiological profile of patients who have undergone surgical therapy of WDTC at HUCAM; obtain oncological outcomes in the follow-up of patients who have undergone surgical therapy, analyze the post-operative complications and compare them with the literature review. Method: A retrospective study with clinical data obtained in histopathological reports filed in electronic registration of the Pathological Anatomy Department of HUCAM/UFES and the analysis of their medical records filed in the Statistical and Medical Archive Service of HUCAM/UFES between January 2008 and December 2015. Results: 95 records of WDTC patients who underwent surgical therapy have been analyzed. Papillary Thyroid Carcinoma (PTC) was the most common (91,57%) and the Follicular Thyroid Carcinoma counted for 8,43% of the cases. The total thyroidectomy was performed in 65,26% of patients, the partial thyroidectomy in 12,63% and the total thyroidectomy combined with neck dissection in 22,11 %. Postoperative complications were observed in 6,31% of the patients. Hemorrhagic complications were observed in 1,05% of the patients. The average follow-up time was 36,9 months. The loco regional recurrence was observed in 4 patients (4,21%) and all of them have undergone surgical therapy once again and have been free of disease. We have analyzed the prognostic factors: gender, age group above 45 years, size of tumor, lymph nodes metastasis, stage of the disease, surgical treatment performed, microcarcinoma, histologic type and post-operative radioactive iodine. There was no statistical significance in relationship with any of the prognostic factors analyzed. Conclusion: WDTC is the most common malignant neoplasm of the thyroid. Women are the group most affected by the disease and the median age was 49 years old. Loco regional recurrence was observed in 4 patients who have been treated and they are free of the disease. The most common post-operative complication was hematoma.